TYPES OF ORGANIZATIONS AND THEIR CHARACTERISTICS - Гассаб, Оксана (SWorldJournal, 2023)
The article is devoted to the study of various types of organizations and their features. Organizations in the modern world can be diverse, and each type has its own characteristics that affect their structure, functions and management methods.The articl